2019
DOI: 10.1186/s12870-019-1903-y
|View full text |Cite
|
Sign up to set email alerts
|

In planta high levels of hydrolysable tannins inhibit peroxidase mediated anthocyanin degradation and maintain abaxially red leaves of Excoecaria Cochinchinensis

Abstract: Background Abaxially anthocyanic leaves of deeply-shaded understorey plants play important ecological significance for the environmental adaption. In contrast to the transient pigmentation in other plants, anthocyanins are permanently presented in these abaxially red leaves, however, the mechanism for the pigment maintenance remains unclear. In the present study, we investigated phenolic metabolites that may affect pigment stability and degradation in Excoecaria cochinchinensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…SGTase can be used as a multiple phenylpropanoid glucosylation enzyme, which exhibited signi cant activity with avonoids [35].β-glucosidase (bglx) was an anthocyanase, which can hydrolyze anthocyanidins into anthocyanin [33]. E1.11.1.7 is a peroxidase that may lead to the degradation of anthocyanin [36]. Above previous studies further con rmed the rationality and reliability of identi ed genes in phalaenopsis from RNA-seq in this study.…”
Section: Discussionsupporting
confidence: 67%
“…SGTase can be used as a multiple phenylpropanoid glucosylation enzyme, which exhibited signi cant activity with avonoids [35].β-glucosidase (bglx) was an anthocyanase, which can hydrolyze anthocyanidins into anthocyanin [33]. E1.11.1.7 is a peroxidase that may lead to the degradation of anthocyanin [36]. Above previous studies further con rmed the rationality and reliability of identi ed genes in phalaenopsis from RNA-seq in this study.…”
Section: Discussionsupporting
confidence: 67%
“…They showed that in human cells the phenolic propyl gallate, synthesized by the condensation of gallic acid and propanol, might, in certain conditions, increase the levels of reactive oxygen species (ROS) and/or promote depletion of protective enzymes or glutathione. Moreover, high (poly)phenol levels can inhibit enzymes such as peroxidases and catalases [ 40 , 41 ]. It is also well known that (poly)phenols from berries can exhibit antimicrobial activity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that both have a relatively higher accumulation within red young leaves in the present research. Recent literature suggests that high levels of hydrolysable tannins [mainly galloylglucoses/ellagitannins (GGs/ETs)] in the young leaves of plants can inhibit POD mediated anthocyanin degradation and can increase stability and color intensity of anthocyanins by copigmentation activity (Luo et al, 2019). Previous studies have also reported that the delayed greening strategy is widespread in the tropics (Coley and Kursor, 1996;Dominy et al, 2002), and that young tropical leaves with visually striking red coloration have a greater increase in chemical defenses compared with mature leaves than do their temperate counterparts (Coley and Aide, 1989).…”
Section: Discussionmentioning
confidence: 99%